Perceptions and Community Participation in The Rebranding of Community-Based Tourism on Gili Iyang Island - Bondan Satriawan; Yufita Listiana (Buletin Ekonomika Pembangunan, 2025)
This study aims to analyze host community perceptions of tourism development on Gili Iyang Island and to examine their implications for community-based tourism rebranding. Specifically, it seeks to: (1) identify local (host) perceptions toward tourism, (2) analyze the social, economic, cultural, and environmental factors shaping these perceptions, (3) evaluate perceived benefits and losses of tourism, and (4) examine changes in community attitudes over time. These objectives are directed toward strengthening community participation in the rebranding process, recognizing that sustainable destination transformation requires local ownership, legitimacy, and active engagement from host communities.The study employs a host perception analysis framework implemented through four stages: perception identification, exploration of influencing factors, evaluation of impacts and benefits, and identification of changes in perceptions and attitudes. Data were collected through a structured questionnaire administered to 100 residents of Gili Iyang Island during July–August 2023. Quantitative descriptive analysis was used to capture patterns of attitudes toward tourists, involvement in tourism, perceptions of change, future expectations, and evaluations of social, cultural, environmental, and economic impacts.Findings indicate that the host community generally holds positive attitudes toward tourism: most residents welcome tourists, perceive ongoing changes as improvements, and express optimism about tourism’s future. Economic impacts are perceived overwhelmingly positively, while social and cultural dimensions reveal ambivalence and concern, particularly regarding cultural erosion. Although 74% of respondents believe tourism benefits outweigh its losses, community participation remains extremely limited, with 92% not yet involved in tourism activities. A significant shift from initial ambivalence to current support demonstrates a critical window for rebranding.  Keywords: Host Perception; Community-Based Tourism; Tourism Rebranding; Gili Iyang